EFISIENSI BIAYA PADA PELAKSANAAN PEMBANGUNAN SYPHON PIPA DAN BETON PADA SALURAN INTERBASIN RABABAKA KOMPLEKS KABUPATEN DOMPU - Ida Bagus Geraldy Winanta Putra; Heri Sulistiyono; Ery Setiawan (Media Bina Ilmiah, 2023)
Implementation of a project is often found the result is not suitable for the conditions at the time of implementation. To overcome this it is necessary to do design adjustments aimed at adjusting the plan of execution with circumstances when the work is implemented. This design adjustment is based on data retrieval directly from existing field conditions by conducting surveys and field engineering. The result of this field engineering will be the basis of calculations for proposed changes in work added/less, volume switching and adding new work items. Construction of reinforced concrete and pipe Steel Carbon ASTM A 252 Grade 2, two types of construction can be applied on the 1. S RBK siphon, but in terms of ease of implementation as well as the ease of supervision, Steel Carbon ASTM A252 Grade 2 pipe construction is more profitable. Calculation result of work implementation of concrete reinforced Syphon is expensive when compared with the work of Syphon by using Steel Carbon ASTM A 252 Grade 2, with efficiency value of 5.14%.